The use of convolution operators in the tasks of edge detection - Петров, Сергій Олександрович; Марченко, Ігор Олександрович; Дібров, Борис Олександрович (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the prevalence of the Kenny algorithm in the edge detection, insufficient attention has been paid to the optimal selection of the convolution matrix. The paper describes typical algorithms to detect the object edges in the image and use the peculiarities of convolution operators in the Kenny algorithm. The research uses a base image size of 13,225 units. Thus, the experiments have proved that the Sobel operator is optimal, in general, for the Kenny algorithm. We have also considered the Roberts operator and the Previtt operator as alternatives and proved that they effectively process individual cases but generally give worse results. We have made a comparative analysis of advantages and disadvantages of all the operators. The paper presents an example of a detailed calculation of the gradient by using the Sobel operator in the Kenny algorithm after the preceding use of the Gaussian filter. The result of the study is verification of the optimal choice of the Sobel operator for the Kenny algorithm.